Association between severe eczema in children and multiple comorbid conditions and increased healthcare utilization. Issue 5 (16th June 2013) - Silverberg, Jonathan I.; Simpson, Eric L.
Abstract: Background: Atopic dermatitis (AD) is associated with multiple comorbid conditions, such as asthma and food allergy. We sought to determine the impact of eczema severity on the development of these disorders and other non‐atopic comorbidities in AD. Methods: We used the 2007 National Survey of Children's Health, a prospective questionnaire‐based study of a nationally representative sample of 91, 642 children aged 0–17 yr. Prevalence and severity of eczema, asthma, hay fever and food allergy, sleep impairment, healthcare utilization, recurrent ear infections, and visual and dental problems were determined. Results: In general, more severe eczema is correlated with poorer overall health, impaired sleep, and increased healthcare utilization, including seeing a specialist, compared with children with mild or moderate disease (Rao‐Scott chi‐squared test, p < 0.0001). Severe eczema was associated with a higher prevalence of comorbid chronic health disorders, including asthma, hay fever, and food allergies (p < 0.0001). In addition, the severity of eczema was directly related to the severity of the comorbidities. These associations remained significant in multivariate logistic regression models that included age, sex, and race/ethnicity. Severe eczema was also associated with recent dental problems, including bleeding gums (p < 0.0001), toothache (p = 0.0004), but not broken teeth (p = 0.04) or tooth decay (p = 0.13). Conclusions: These data indicate that severe eczema is associated with multiple comorbid chronic health disorders, impaired overall health, and increased healthcare utilization. Further, these data suggest that children with eczema are at risk of decreased oral health. Future studies are warranted to verify this novel association. Abstract :